Current Trends in Otorhinolaryngology and Head and Neck Pathology - Neagos, Adriana; Vrinceanu, Daniela; Sarafoleanu, Codrut; Kalcioglu, Mahmut Tayyar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Otorhinolaryngology and head and neck specialists worldwide face an increasing incidence and prevalence of various pathologies, some of the cases neglecting the evolution of their condition during the period of COVID-19 pandemics, thus aggravating their evolution. This Special Issue contains reviews and selected rare case series to update the protocols of ENT and allied specialists worldwide. The aim was to present an interdisciplinary point of view of the numerous branches of pathology that form the otorhinolaryngology specialty.